2019
DOI: 10.1021/acsami.8b19111
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of Cu2O to Cu2O@Cu-Metal–Organic Frameworks for Selective Electrochemical Reduction of CO2

Abstract: Electrochemical reduction of carbon dioxide to hydrocarbons, driven by renewable power sources, is a fascinating and clean way to remedy greenhouse gas emission as a result of overdependence on fossil fuels and produce value-added fine chemicals. The Cu-based catalysts feature unique superiorities; nevertheless, achieving high hydrocarbon selectivity is still inhibited and remains a great challenge. In this study, we report on a tailor-made multifunction-coupled Cu-metal–organic framework (Cu-MOF) electrocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(122 citation statements)
references
References 40 publications
5
117
0
Order By: Relevance
“…Stability is one of the most concerning issues facing the CO 2 ER. Whilst most authors have claimed that pristine MOFs that are based on readily reducible metals are stable under CO 2 ER reaction conditions, catalyst stability has only been confirmed in a few cases by using post‐analysis characterization . Herein, we would like to clarify that the stability of the crystalline MOF does not necessarily need to be an issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability is one of the most concerning issues facing the CO 2 ER. Whilst most authors have claimed that pristine MOFs that are based on readily reducible metals are stable under CO 2 ER reaction conditions, catalyst stability has only been confirmed in a few cases by using post‐analysis characterization . Herein, we would like to clarify that the stability of the crystalline MOF does not necessarily need to be an issue.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Tan et al. synthesized a tailor‐made Cu 2 O@Cu‐MOF electrocatalyst through the in situ etching of Cu 2 O spheres with H3BTC to form a Cu‐MOF shell . The as‐prepared electrocatalyst exhibited intriguing performance for the formation of hydrocarbons from CO 2 , with a high FE for CH 4 and C 2 H 4 of 79.4 %, and especially a FE for CH 4 of up to 63.2 % at −1.71 V.…”
Section: Mof‐related Catalysts For Co2ermentioning
confidence: 99%
“…[ 121 ] Tan et al reported a Cu 2 O@Cu‐MOF restructured catalyst with a unique CO 2 ‐adsorption ability and demonstrated outstanding performance with a total FE of 79.4% toward hydrocarbon products. [ 122 ] Figure 8d shows a schematic illustration of the process of Cu 2 O@Cu‐MOF catalyst synthesis. Based on the TEM and HRTEM images of the catalyst, shown in Figure 8e,f, the residual oxidized Cu derived from the Cu + species on the surface of initially formed Cu 2 O nanospheres that fully coated the Cu‐MOF, wherein trimesic acid (H 3 BTC) functioned as both an etching agent and an organic ligand for the formation of the Cu‐MOF hybrid.…”
Section: Surface Structure‐dependent Catalytic Activity/selectivity Omentioning
confidence: 99%
“…CH4, C2H6, and other products were also reported in the study. Similarly in 2019, Tan et al [12] developed a novel metal organic framework in Cu2O-based electrodes and reported improved faradaic efficiency towards CH4 while also producing other higher order carbon products.…”
Section: Graphical Abstract Introductionmentioning
confidence: 97%
“…The surface porosity in electrode structures has been reported to change both reagent and product transport pathways [17] and these changes in transport phenomena have shown to increase current density and change product selectivity [18,19]. Since most studies have used smaller sizes of Cu2O particles in combination with either copper metal [20][21][22][23] or glassy carbon [12,24], it was our hypothesis that the use of larger size of Cu2O particles supported on a structurally porous CP substrate would offer new product distributions.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%